2018
DOI: 10.1007/s10570-018-2131-6
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the chemistry of cellulosic key chromophores

Abstract: The chemistry of cellulosic key chromophores is challenging because of the usually very low concentration of the colored compounds in realworld cellulosic matrices. It offers many surprises and positive outcomes; unfortunately there are also pitfalls and disappointments. This report discusses eight examples or surprising chemistry out of the realm of cellulosic key chromophores. The reactions have either taken unforeseen paths or provided unexpected products. The reaction mechanisms of the ''strange'' processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Follow-up studies to our investigations on DHBQ in the chromophore chemistry of cellulosic fibers [17,18] showed that DHBQ and urea formed 1H-benzo[d]imidazole-2,5,6(3H)-trione (9) with the two quinone-carbonyls remaining non-derivatized. Thus, the formation of an aromatic or conjugated system could not be the decisive factor, otherwise urea would rather have formed the corresponding -hypothetical -ortho-quinone diimine structure.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Follow-up studies to our investigations on DHBQ in the chromophore chemistry of cellulosic fibers [17,18] showed that DHBQ and urea formed 1H-benzo[d]imidazole-2,5,6(3H)-trione (9) with the two quinone-carbonyls remaining non-derivatized. Thus, the formation of an aromatic or conjugated system could not be the decisive factor, otherwise urea would rather have formed the corresponding -hypothetical -ortho-quinone diimine structure.…”
Section: Resultsmentioning
confidence: 91%
“…Benzo[c][1,2,5]thiadiazole-5,6(1H,3H)-dione 2,2-dioxide (18), orange crystals, m.p. = 180-181°C, yield 99.3%, purity (GCMS): 99.8%.…”
Section: Reaction With Sulfamidementioning
confidence: 99%
“…Sample coloration derives from the acid degradation of the xanthan and cellulose polymers 35,36 and chromophore formation in the presence of glyoxal. 37 During preparation before the cross-linking step at 140°C and after drying over-night the samples are uncoloured.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RhA salts are virtually insoluble and tend to precipitate on the walls and bottom of the cuvette, even at concentrations as low as 1 lM. GC-MS was not an option either: the reaction had to be stopped reliably, and the sample had to be dried and derivatized, which did not work quantitatively for either compound (Hettegger et al 2019). The rapid neutralization with excess sodium sulfite solution and subsequent UV/Vis measurement of the resulting alkaline solution at 310 nm worked very well and was the method of choice.…”
Section: Model Compound Experimentsmentioning
confidence: 99%